The Impact of Type 2 Diabetes on the Efficacy of ADP Receptor Blockers in Patients with Acute ST Elevation Myocardial Infarction: A Pilot Prospective Study - Matej Samoš; Marián Fedor; František Kovář; Peter Galajda; Tomáš Bolek; Lucia Stančiaková; Jana Fedorová; Ján Staško; Peter Kubisz; Marián Mokáň (Journal of Diabetes Research)
Background. The aim of this study was to validate the impact of type 2 diabetes (T2D) on the platelet reactivity in patients with acute ST elevation myocardial infarction (STEMI) treated with adenosine diphosphate (ADP) receptor blockers. Methods. A pilot prospective study was performed. Totally 67 patients were enrolled. 21 patients had T2D. Among all study population, 33 patients received clopidogrel and 34 patients received prasugrel. The efficacy of ADP receptor blocker therapy had been tested in two time intervals using light transmission aggregometry with specific inducer and vasodilator-stimulated phosphoprotein phosphorylation (VASP-P) flow cytometry assay. Results. There were no significant differences in platelet aggregability among T2D and nondiabetic (ND) group. The platelet reactivity index of VASP-P did not differ significantly between T2D and ND group (59.4±30.9% versus 60.0±25.2% and 33.9±25.3% versus 38.6±29.3% in second testing). The number of ADP receptor blocker nonresponders did not differ significantly between T2D and ND patients. The time interval from ADP receptor blocker loading dosing to the blood sampling was similar in T2D and ND patients in both examinations. Conclusion. This prospective study did not confirm the higher platelet reactivity and higher prevalence of ADP receptor blocker nonresponders in T2D acute STEMI patients.